Family Planning Unmet Need; Determinant Factors and Strategy Design through Health Management Approach and Fishbone Analysis in Riau Province, Indonesia - Ismainar, Hetty; Mishbahuddin, Mishbahuddin (Technium Social Sciences Journal, 2021)
The high number of unmet needs for Family Planning (FP) in Indonesia has an effect on birth spacing and the number of parities so that there is a high risk of maternal and infant mortality. Based on data from the Family-Program Performance and Accountability Survey (PPAS) from the National Population and Family Planning Board (NPFPB) in 2019, 51% of Fertile Age Women (FAW) were not willing to use FP. This study aims to describe the determinant factors and strategies to reduce the incidence of unmet needs for FP. The method used was a quantitative descriptive study conducted in July-September 2021. The data collection technique analyzed the program performance and accountability survey report data from NPFPB in 2019 (secondary data). The result was that the determinant factors of the unmet need for FP include: age 30-49 years (60.1%), parity having 6 or more children (73.6%), reasons for fertility (32.89%), being against using (7.9%), lack of knowledge about 8 modern FP tools/methods (15.5%), reasons for FP tools/methods (34.65%). Meanwhile, the majority of information on FP was obtained through television (91.9%), direct information through midwives/nurses (77.5%). The strategy to reduce the number of unmet need for FP was through a health management approach with five stages, namely: 1. Assessment to identify the number of Fertile Age Couple (FAC) unmet need for FP, demographic characteristics, and reasons for not using contraceptive tools/methods: 2. Mapping step, case mapping per region, 3. Planning, service planning process, 4. action, service delivery based on planning, 5. Evaluation monitoring stage, monitoring process, and activity evaluation. Six management elements are used for fishbone analysis, namely: man, money, method, material, machine, and market. It requires a high commitment to all stakeholders so that the implementation of the strategy can be realized.